ChemInform Abstract: An Efficient Synthesis of Trisubstituted Oxazoles via Chemoselective O‐Acylations and Intramolecular Wittig Reactions. Issue 9 (4th March 2014) - Tsai, Yi‐Ling; Fan, Yu‐Shiou; Lee, Chia‐Jui; Huang, Chan‐Hui; Das, Utpal; Lin, Wenwei
Abstract A general procedure for the synthesis of highly substituted oxazoles (III), (V)/(VI), and (VIII) from acyl imines (I) is described.